Differences in phagocytosis and killing by alveolar macrophages from humans, rabbits, rats, and hamsters. - Nguyen, B Y (American Society for Microbiology (ASM), 1982)
Phagocytosis and killing by alveolar macrophages from humans, rabbits, rats, and hamsters, were compared in vitro. In the absence of serum opsonins, human alveolar macrophages could phagocytize Staphylococcus aureus Cowan I (protein A positive), but not S. aureus EMS (protein A negative) or Pseudomonas aeruginosa MN. In contrast, rabbit, rat, and hamster alveolar macrophages did not phagocytize S. aureus Cowan I or other nonopsonized bacteria. Human alveolar macrophages, but not other species, stained positively with fluorescein isothiocyanate-conjugated protein A. When opsonized bacterial were studied, phagocytosis by human, rabbit, and hamster alveolar macrophages was found to be mediated by both Fc and C3 receptors. However, only Fc receptor-mediated phagocytosis of bacteria was demonstrated for rat alveolar macrophages. Differences were also found in the kinetics of bacterial killing by alveolar macrophages from different species. Human and rabbit alveolar macrophages rapidly killed opsonized S. aureus Cowan I. However, bacterial killing by hamster alveolar macrophages proceeded at a slower rate, and rat alveolar macrophages completely failed to kill S. aureus. These significant differences in the function of alveolar macrophages from four different species emphasize the need to document the appropriateness of animal models before using them to predict the biological activities of human alveolar macrophages.